El crecimiento empresarial vía cooperaciones entre compañías. Estudio empírico sobre el sector turístico español. - Martín-Rojo, Inmaculada Concepción; Gaspar-González, Ana Isabel (AEDEM, 2007)
The present globalized environment arises important challenges to SME and big companies. This paper analyzes the cooperation as a growth way to adapt to the new scene, defining this investigation to the spanish tourist sector. After doing an introduction about spanish enterprises composition according to the dimension of the companies, and present a brief conceptual framework and the state of the subject about cooperation, an empirical research about enterprise growth in spanish tourist sector utilizing Delphi method is exposed, and basing on the reached results, a serie of proposals is suggested in order to achieve sinergies between companies of different dimensions, starting from the establishment of business network.
Alojada en Dialnet y Econstor.
Keywords: Globalización (Economía); Turismo - Aspectos económicos; Cooperación empresarial; Globalización; Crecimiento empresarial; Acuerdos de cooperación; Redes de empresas; Sector turístico